Circular dichroism spectrum of (R)-(+)-3,3′-dibromo-1,1′-bi-2-naphthol in albumin: Alterations caused by complexation—Experimental and in silico investigation - Ximenes, Valdecir Farias [UNESP]; Yoguim, Maurício Ikeda [UNESP]; de Souza, Aguinaldo Robinson [UNESP]; Morgon, Nelson Henrique (Wiley, 2024)
This study describes the interaction of human serum albumin (HSA) with the binol derivative (R)-(+)-3,3′-dibromo-1,1′-bi-2-naphthol (R-BrB), which has its optical activity based on the prohibitive energetic barrier for conversion into the enantiomer (S)-(+)-3,3′-dibromo-1,1′-bi-2-naphthol (S-BrB). The objective was to assess the ability of HSA to differentiate axial enantiomers based on their binding efficiency and their impact on the CD spectra. We discovered that both enantiomers were effective ligands, and the CD signal disappeared when equimolar amounts of R-BrB and S-BrB were simultaneously added, indicating no preference for either enantiomer. The complexation resulted in a significant signal increase at 250 nm and a bathochromic effect at 370 nm. Molecular docking simulations were performed, and the lower energy pose of R-BrB was selected for DFT calculations. The theoretical CD spectra of free and complexed R-BrB were obtained and showed alterations corroborating the experimental results. By comparing the difference spectrum (HSA:R-BrB minus HSA) with the spectrum of free RBrB in water or ethyl alcohol, we concluded that the CD signal intensification was due to the increased solubilization of R-BrB upon binding to HSA.
Keywords: albumin; binols; DFT; ibuprofen; molecular docking; warfarin